Repetitive transcranial magnetic stimulation of the primary motor cortex in the treatment of motor signs in Parkinson's disease: A quantitative review of the literature. Issue 6 (18th March 2015) - Zanjani, Anosha; Zakzanis, Konstantine K.; Daskalakis, Zafiris J.; Chen, Robert
Abstract Parkinson's disease (PD) is a progressive disorder characterized by the emergence of motor deficits. In light of the voluminous and conflicting findings in the literature, the aim of the present quantitative review was to examine the effects of repetitive transcranial magnetic stimulation (rTMS) targeting the primary motor cortex (M1) in the treatment of motor signs in PD. Studies meeting inclusion criteria were analyzed using meta‐analytic techniques and the Unified Parkinson's Disease Rating Scale (UPDRS) sections II and III were used as outcome measures. In order to determine the treatment effects of rTMS, the UPDRS II and III scores obtained at baseline, same day, to 1 day post rTMS treatment (short‐term follow‐up) and 1‐month post stimulation (long‐term follow‐up) were compared between the active and sham rTMS groups. Additionally, the placebo effect was evaluated as the changes in UPDRS III scores in the sham rTMS groups. A placebo effect was not demonstrated, because sham rTMS did not improve motor signs as measured by UPDRS III. Compared with sham rTMS, active rTMS targeting the M1 significantly improved UPDRS III scores at the short‐term follow‐up (Cohen's d of 0.27, UPDRS III score improvement of 3.8 points). When the long‐term follow‐up UPDRS III scores were compared with baseline scores, the standardized effect size between active and sham rTMS did not reach significance. However, this translated into a significant nonstandardized 6.3‐point improvement on the UPDRS III. No significant improvement in the UPDRS II was found. rTMS over the M1 may improve motor signs. Further studies are needed to provide a definite conclusion. © 2015 International Parkinson and Movement Disorder Society